Spirodesma magdae nov. gen. nov. sp. (Nematoda: Desmodoridae) from the Brazilian deep sea (Campos Basin, Rio de Janeiro, Brazil) - Da Fonseca Cavalcanti, M.; Da Silva, M.C.; Da Fonseca-Genevois, V. (Zootaxa, 2009)
A new genus and species of Desmodoridae was found in deep-sea sediments of the Campos Basin. Although the cuticle annulation of the new species is similar to members of Desmodorinae, many morphological features are strong enough to classify it within the Spiriniinae. Spirodesma magdae nov. gen. nov. sp. is characterized mainly by the presence of a unique form of unispired amphids, with circular amphideal fovea, and a buccal cavity with three equal teeth, one dorsal and two ventrosublateral.
NeMys doc_id: 17895